Liminality, transformation and communitas : Afrikaans identities as viewed through the lens of South African Arts Festivals: 1995 – 2006 - Van Heerden, Esther (Stellenbosch : University of Stellenbosch, 2009)
Thesis (DPhil (History))—University of Stellenbosch, 2009.